Hukuman Mati Bagi Pengedar Narkoba - Adi Syahputra Sirait, Tuti Amma Sari Siregar & Ahmatnijar & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
As for the academic problem, it is find out how the death penalty for drug traffickers is in law number 35 of 2009 and how the death penalty for drug dealers in jinayah fiqh. The type of research, which is carried out by reviewing and examining various documents in the form of books or writings related to the problem. The approach used in this research is a normative juridical approach, namely an approach that examines the problems of the law and then resolves these problems with fiqh jinayah. The result of this research is that the death penalty in law number 35 of 2009 concering drugs is applied to the act of offering for sale, selling, buying, being an intermediary in buying and selling, exchanging, surrendering, or receiving class 1 narcitics in the types of marijuana, heroin, cocaine, morphine, opium, shabu-shabu provided that the weight in the form of plants exceeds 1 kilogram, or exceeds 5 trees or in non-plant form, the weight exceeds 5 grams. Then the execution of the death penalty in article 11 of the criminal code was by hanging and in presidential decree number 2/PNPS/1964 by being shot dead. A review of jinnayah fiqh is a person who can be sentenced to death if he commits a crime from one of the following three criminal acts: deliberate murder, zinamuhson, and apostasy. So tht the death penalty in drug cases applied in Indonesian thtough law number 35 of 2009 concerning drugs is not mentioned, but if it is reviewed from Magoshid As-Syariah, Maslaha and also Sadd Adz-Dzariah, the death penalty can be applied to dealers. Drugs because of the many damages they cause, the presidential decree is part of ta’zir.